Reduced menthol sensitivity in a prodromal Parkinson’s disease model induced by intranasal rotenone treatment - Sato, Hajime; Satoh, Keitaro; Nozaki, Kazunori; Yugawa, Misato; Kato, Takafumi; Toyoda, Hiroki; Katagiri, Ayano; Suda, Naoto; Adachi, Kazunori (Frontiers in Cellular Neuroscience, 2024)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by motor symptoms, and it is associated with several prodromal non-motor symptoms, including an impaired sense of smell, taste and touch. We previously reported that bitter taste impairments occur independently of olfactory impairments in an early-stage PD animal model using short-term intranasal rotenone-treated mice. Cool temperatures also affect bitter taste perception, but it remains unclear whether or not bitter taste impairments result from an altered sensitivity for intraoral cool stimuli. We examined disturbances in the intraoral menthol sensitivity, such as coolness at low concentrations of menthol, using a brief-access test. Once a day, one solution from the 7-concentration series of (-)-menthol (0-2.3 mM) or the bitter taste quinine-HCl (0.3 mM) was randomly presented 20 times for 10 s to water-deprived mice before and 1week after rotenone treatment. The total number of licks within 20 times was significantly decreased with the presentation of 2.3 mM menthol and quinine-HCl, compared to distilled water in untreated mice, but not in rotenone-treated mice. The correlation between the licks for quinine-HCl and that for menthol was increased after rotenone treatment. In contrast, the 2-bottle choice test for 48 h clarified that menthol sensitivity was increased after rotenone treatment. Furthermore, a thermal place preference test revealed that seeking behavior toward a cold-floored room was increased in the rotenone-treated mice despite the unchanged plantar cutaneous cold sensitivity.These results suggest that taste impairments in this model mice are at least partly due to intraoral somatosensory impairments, accompanied by peripheral/central malfunction.